2015
DOI: 10.1111/1471-0528.13553
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome after fetoscopic laser surgery for twin‐to‐twin transfusion syndrome in triplet pregnancies

Abstract: Objectives The introduction of fetoscopic laser surgery of placental anastomoses has led to a significant improvement of perinatal outcome of twin pregnancies affected by twin-to-twintransfusion syndrome (TTTS). To quantify the perinatal outcome and neurological morbidity in triplet pregnancies complicated by TTTS, which were treated with fetoscopic laser surgery.Search strategy Medline, Embase, Cinahl and Cochrane were searched.Selection criteria The outcomes observed were: fetal and perinatal survival, prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…In our study, the incidence of TTTS in dichorionic triplets was 12.6%. Fetal and perinatal survival rates are lower in triplets than those reported for twin pregnancies 26 .…”
Section: Interpretation Of Findings and Comparison With Existing Litementioning
confidence: 57%
See 1 more Smart Citation
“…In our study, the incidence of TTTS in dichorionic triplets was 12.6%. Fetal and perinatal survival rates are lower in triplets than those reported for twin pregnancies 26 .…”
Section: Interpretation Of Findings and Comparison With Existing Litementioning
confidence: 57%
“…In our study, the incidence of TTTS in dichorionic triplets was 12.6%. Fetal and perinatal survival rates are lower in triplets than those reported for twin pregnancies. Although survival of the unaffected triplet is not usually compromised by the hemodynamic imbalance occurring in the monochorionic pair, the entire pregnancy may be at risk of miscarriage or early preterm labor.…”
Section: Discussionmentioning
confidence: 89%
“…However, with the accumulation of data and improvement in surgical skills over the years, more recent studies, including our cohort study and systematic review, have demonstrated no difference in survival between DCTA and MCTA triplets. Moreover, compared with a meta‐analysis published in 2016 10 , our systematic review showed a higher rate of fetal survival in MCTA triplet pregnancies, including fetal survival of at least two (90% vs 85%) and three (53% vs 39%) triplets. Although the difference in median FLP‐to‐delivery interval was not significant, it was 38 days longer in MCTA triplets, which might have improved survival outcomes.…”
Section: Discussionmentioning
confidence: 55%
“…The survival rate of both twins has increased from 35% to 65% with the use of FLP in MC twin pregnancies 8 . In addition, FLP significantly improved the postnatal neurological outcome compared with that of the more conventional treatment approach of amnioreduction 9 , and a promising role of FLP has been reported in numerous studies 10,11 . Management options and survival of triplets with TTTS are frequently discussed in the literature 12–15 .…”
Section: Introductionmentioning
confidence: 99%
“…This seems somewhat lower than the 8%–17.6% and 10%–15% that was previously reported in MCTA triplets and MCDA twins respectively, 11,18,19 which need further large sample and collaborative evaluation in the future. A recent systematic review about the perinatal outcome after fetoscopic laser surgery for TTTS in 22 MCTA triplets revealed that all three fetuses survived in 48.4% of the pregnancies and at least one triplet survived in 88.9% pregnancies, indicating that this technique is feasible for treatment of this condition 20 . Similarly, our MCTA triplet with TTTS was treated successfully with endoscopic laser and continued to delivery with 3 live fetuses.…”
Section: Discussionmentioning
confidence: 59%